Educational reform and role of the government regarding the decentralization of the brazilian educational policies - Valadão, Adriana (2015)
This study has the goal of comprehending the process of decentralization of the educational policies on the municipality management, aiming at the identification of the autonomy of the municipality on the elaboration and implementation of the Joint Action Plan (PAR) in four different locations in the state of Mato Grosso do Sul, Brazil, in the period 2007-2010, technically and financially supported by the Union. The methodology is based both on quantitative and qualitative aspects and uses documental and content analysis as tools. The research shows how the planning on the municipal level and on the federal level are at variance with each other, evidencing that the decentralization has not been achieving the expected results regarding the autonomy given to the municipalities on the local educational management. This is due to the strong centralization exerted by the Union on the implementation of the educational policies through financial control over the resources directed first to the programs and projects on a federal scale.